Tagi Jere Tradition: Its Function and Preservation as A Cultural Identity of Tidore People in Foramadiahi - Safi, Jamin; Bau, Suharlin Ode; A. Boko, Yusri (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2024)
Tagi Jere in the Tidore language means to visit the tomb of a saint. This ritual usually begins with certain preparations and is then followed by a visit to the Jere such as Jere Sultan Babullah, Jere Doe-doe, Jere Laboso, Jere Amo, Jere Tui, and Jere Wange Lamo. Tagi Jere is carried out as an expression of gratitude to God for the blessings that have been given. In addition, the Tagi Jere ritual is also carried out under certain conditions, such as crop failure, or as an antidote to distress or disaster. The researcher was interested in seeing the Tagi Jere ritual in the Tidore ethnic community in Ternate, especially in the Foramadiahi sub-district, using a qualitative approach. The interpretation of the data in the field shows that the Tagi Jere ritual is used as a request by the community based on their respective intentions. They brought Boso Kene (small pots of earthenware) containing Bira Kuraci (yellow rice) which they brought to the visited Jere. The Tagi Jere ritual also has a social value to strengthen the bonds of brotherhood that are manifested in mutual cooperation activities. The rituals performed by the Tidore ethnic community in various circles are preserved from generation to generation.